Computationally guided optimization of the antimalarial activity and physicochemical properties of 2,4-diaminopyrimidines - Guntur Guntur; Duangkamol Gleeson; Mark Anderson; Nicole Mutter; Lauren Webster; Kevin D. Read; M. Paul Gleeson (RSC Medicinal Chemistry, 2025)
).
Keywords: Computational Drug Discovery Methods; Synthesis and biological activity; Synthesis and Characterization of Heterocyclic Compounds